Safety And Efficacy Of Drug-Coated Balloon In Large Coronary Artery Disease - Haroon, Saleha; Shahid, Hafsa; Javed , Asim; Raja , Tanveer Ahmed; Pirzada, Naveed; Rehman, Abdur (Journal of Rawalpindi Medical College, 2025)
Introduction: Coronary artery disease is one of the leading causes of death worldwide for which various therapeutic interventions have been proposed. The use of drug-coated balloons (DCBs). DCBs have gained attention as a promising tool for the treatment of large coronary artery disease. This study aims to see the efficacy and clinical outcomes of DCB therapy in large coronary artery disease. Methods: This prospective observational study involving 60 patients of CAD, was conducted in the Department of Cardiology, Rawalpindi Institute of Cardiology, Rawalpindi. The patients with large coronary artery disease were included and treated with DCB therapy. The effectiveness of DCB as the primary outcome in terms of target lesion revascularization was observed over time. Similarly secondary (adverse outcomes) were also assessed and represented as frequencies and percentages. Analysis was done by SPSS.V.26. Results: In our study, the mean age was 55.217±9.814 and the mean diameter of the target vessel was 3.1 ± 0.249 mm while that of the lesions was 25.25 ± 8.1 mm. On follow-up, target lesion revascularization was noted in only 8 (13.3 %), similarly, the adverse outcomes like MI in 4 (6.7%), target vessel thrombosis in 5 (8.3%), dyspnea in 8 (13.3%), effort angina in 10 (16.7%), and death was reported in just 2 (3.3%) of the patients. Conclusion: The use of DCB therapy resulted in a significant reduction in the proportion of patients requiring target lesion revascularization, which was the primary outcome measure. Furthermore, the secondary (adverse) outcomes exhibited a notable decrease in patients who received DCB therapy, thus demonstrating the efficacy of DCB therapy in individuals with large coronary artery disease.